PENGARUH EARNING PER SHARE, DIVIDEND PER SHARE, DAN STOCK SPLIT TERHADAP PERUBAHAN HARGA SAHAM - Natsir, Muh (Jurnal Analisis Bisnis Ekonomi, 2007)
A sophisticated investor must be having sensitivity for about information when they was invested in securities market. That information are trusted can be influenced a price change stock. The aim of examination is to analyze three independent variable that included earning pr share, dividend per share, and stock split in a partial manner or in simultan manner. The populations of examination in a enterprise included a financial sector that list at Jakarta Stock Exchange from 2003-2005. the act of determining sample with a purposive sampling method, there are six enterpise that included criteria of samples. The testing hypothesis with a opponent of regression linear model. The result of analysis directed that a partial manner, coefficient regression of earning per share in the 0,352, dividend per share in the 0,050 having influence positive to a price change stock, and stock split in the -0,170 having negative influence to a price change stock. In a simultan earning per share, dividend per share and stock split having significant influence to a price change stock.